PROFIT SHARING SYSTEM AND COMPARATIVE INCOME OF RUBBER FARMING BUSINESS IN NURUSSALAM DISTRICT, EAST ACEH REGENCY - Deva Septiana Siregar; Mawardati Mawardati; Irada Sinta (LPPM Universitas Malikussaleh - Indonesia, 2024)
The form of cooperation in farming is a profit-sharing system, namely the cooperation between the owner of the rubber plantation as the owner of the cultivator and the cultivator. In the implementation of this profit sharing, the owner of the rubber plantation as the cultivator and the passive farmer make an agreement in advance. However, in the application of agribusiness farming applied by rubber farmers in Nurussalam District, not all owners carry out all farming activities, among others, on the grounds that they are unable to carry out these activities or want to help workers who do not have business land but have the ability to do farming.This research was conducted in Nurussalam District, East Aceh Regency. The study aims to identify the system to distinguish between the farmers who owned the cultivators and the farmers of disease and the income differences between the cultivators and the diseases in the district of Aceh. The method of data analysis used is qualitative and quantitative descriptive. This study showed that the system for the results done by rubber farmers in the Aceh region was 50:50, which means 50% for garden owners and 50% for disease farmers. The average income produced by the cultivator will grow Rp. 23,083,955.35 /ha and the average profit from the ill farmers Rp. 23,852,354.70 /ha, and the results from the statistical test indicate a significant value (2-tailed) 0.673 > 0.05, which means that the hypothesis is rejected which states that there is no significant difference in income from rubber farming between sharecroppers and smallholders in Nurussalam sub-district, East Aceh district.